Hospital care for adults with cystic fibrosis: an overview and comparison between special cystic fibrosis clinics and general clinics using a patient questionnaire. - Walters, S. (1994)
BACKGROUND--Provision of medical care for adult patients with cystic fibrosis is an increasing problem as the number of patients surviving into adulthood increases. Recent reports have suggested that care is best provided in specialist centres because of longer survival. Recent changes in the National Health Service funding and delivery of service may adversely affect the provision of such a specialist service. The aim of this study was to assess the current pattern of medical service received by adults with cystic fibrosis and to compare the type of care between special cystic fibrosis and general clinics. METHODS--Confidential postal questionnaires were sent to all 1052 members of the Association of Cystic Fibrosis Adults (ACFA) comprising 59% of the UK population of cystic fibrosis patients over 15 years and 80% over 25 years of age. The response rate was 82%. RESULTS--Two thirds of patients were attending special cystic fibrosis clinics for either adults or adults and children. There were significant differences in the proportion of patients using special cystic fibrosis clinics between regions but not between social class groups. Significant differences between cystic fibrosis and general clinics were noted. Patients attending cystic fibrosis clinics were more likely to have had simple clinical investigations (blood tests, sputum culture, oxygen saturation, chest radiography, weight and lung function measurement) in the previous year. They were also more likely to have received intravenous antibiotics at home, and to have access to paramedical personnel. Patients attending cystic fibrosis clinics were taking higher doses of pancreatic enzyme supplements with respect to quantity and potency of preparation. Such patients also had less severe symptoms irrespective of social class, and were more likely to be satisfied with professional aspects of their care. Regardless of type of clinic, potential deficiencies were identified in overall medical care with omission of clinical investigations in severely affected patients and evidence of undertreated respiratory and digestive symptoms in patients with moderate and severe disease. CONCLUSIONS--This survey provides evidence that adults with cystic fibrosis attending special cystic fibrosis clinics receive more intensive care, have better symptom control, and are more satisfied with the service provided than those attending general clinics.